TEXTS OF VARIOUS GENRES AS THE METHODOLOGICAL BASIS OF THE SUBTEST “READING” OF THE FIRST CERTIFICATION LEVEL OF THE RSL EXAM - Bodrova, Tatyana; Zubanova, Svetlana; Kruchkovich, Sofia (Revista Inclusiones, 2021)
Studying Russian as a foreign language during the pre-university courses of Russian universities involves the final test passing. The subtests “Reading” are difficult for foreigners according to some practice. Studying Russian as a foreign language during the pre-university courses of Russian universities involves the final test passing. The subtests “Reading” are difficult for foreigners according to some practice. The article considers the problem of various genre text use as the methodological basis for the development of the subtest “Reading” during the exam in Russian as a foreign language of the I certification level. The authors of the article give several examples of this type of tasks that can be used in practical work by RAF teachers of various universities.